Estudio comparativo presupuestario del cuerpo de bomberos municipal del cantón Babahoyo en el periodo 2021-2022. - Velarde Lombeida, Guisella Elizabeth (2023)
Among the institutions that are placed at the service of the citizenry, all localities must have an organization that performs the assigned function, such is the case of the Municipal Fire Department of the Babahoyo canton, it is based on providing prevention, defense , relief and firefighting; also providing support in disasters of natural origin or generated by the human being; for which it requires a budget that covers the expenses incurred by the association, therefore the purpose of this study lies in carrying out a comparative study of the entry and exit budget documents executed both for the year 2021 and 2022. Regarding the management of budgets, the Fire Department within the aforementioned periods has had an imbalance in its balances, the income it receives from the institutions that financially support its operation have delays, this causes a negative impact on the fulfillment of its objectives that are drawn for the established times. Its methodology had a descriptive, bibliographic, inductive and deductive approach, and as a technique an interview and comparative documentary analysis of the budgetary documents of the institution were applied. It was concluded that, in the year 2022, the expenses were higher compared to those that occurred in the year 2021, as well as the difference in income of both periods.